PEMIKIRAN AMINAH WADUD TENTANG RELASI KUASA DALAM RUMAH TANGGA - Adib, M. Afiqul (UIN Sunan Kalijaga Yogyakarta, 2024)
Gender injustice and inequality often arise in patriarchal family relationships that dichotomize the roles of men (husbands) and women (wives) within the household. This study aims to analyze Aminah Wadud's perspective on the imbalance of power relations in the household based on her interpretation of the Quran. This research uses the library research method, focusing on various relevant sources and references about Aminah Wadud's views on gender studies in the Quran and their application in the context of household relationships. The theoretical framework underlying this research is Islamic feminism, which is used to understand how Quranic interpretation can shape or challenge patriarchal structures within the family. The results show that Aminah Wadud emphasizes the importance of an egalitarian and inclusive interpretation, highlighting justice and gender equality within the household. Wadud's views provide new insights into the role of the Quran in forming fairer and more equal gender relations in society, offering a framework to reassess traditional interpretations that are often gender-biased. This study also reveals that more progressive and contextual interpretations of sacred texts can contribute to forming more just and equal social norms. The findings of this research are expected to serve as an important reference for academics and practitioners in developing strategies to reduce gender inequality in the context of both household and broader society. Keyword: Power Imbalance; Gender Study; Aminah Wadud. Ketidakadilan dan ketidaksetaraan gender sering muncul dalam pola relasi keluarga patriarkis yang mendikotomikan peran antara laki-laki (suami) dan perempuan (istri) dalam rumah tangga. Studi ini bertujuan untuk menganalisis pandangan Aminah Wadud terhadap ketimpangan relasi kuasa dalam rumah tangga berdasarkan penafsirannya terhadap Alquran. Penelitian ini menggunakan metode library research dengan fokus pada penelusuran berbagai sumber dan referensi yang relevan tentang pandangan Aminah Wadud terkait kajian gender dalam Alquran dan aplikasinya dalam konteks relasi rumah tangga. Teori yang mendasari penelitian ini adalah teori feminisme Islam, yang digunakan untuk memahami bagaimana interpretasi Alquran dapat membentuk atau menantang struktur patriarki dalam keluarga. Hasil penelitian menunjukkan bahwa Aminah Wadud menekankan pentingnya tafsir yang egaliter dan inklusif, yang menekankan keadilan dan kesetaraan gender dalam rumah tangga. Pandangan Wadud memberikan wawasan baru mengenai peran Alquran dalam membentuk relasi gender yang lebih adil dan setara dalam masyarakat, sekaligus menawarkan kerangka kerja untuk mengkaji ulang interpretasi tradisional yang sering kali bias gender. Studi ini juga mengungkapkan bahwa penafsiran yang lebih progresif dan kontekstual terhadap teks-teks suci dapat berkontribusi pada pembentukan norma-norma sosial yang lebih adil dan setara. Temuan penelitian ini diharapkan dapat menjadi referensi penting bagi akademisi dan praktisi dalam mengembangkan strategi untuk mengurangi ketimpangan gender dalam konteks rumah tangga dan masyarakat luas. Kata kunci: Ketimpangan Kuasa; Kajian Gender; Aminah Wadud.